Enhancing ECN's abilities to address inventive strategies using OTSM-TRIZ. (27th July 2009) - Khomenko, Nikolai; De Guio, Roland; Cavallucci, Denis
This paper analyses and discusses from various points of views to what extent Theory of Inventive Problem Solving (TRIZ) and its generalisation (OTSM) could contribute to the Engineering as Collaborative Negotiation (ECN) process instrumentation and evolution. First, decision-making and optimisation approach are compared with OTSM-TRIZ problem stating approach and overall strategies to perform steps of the ECN process are deduced. Then, it is briefly shown how OTSM-TRIZ deals with exploration and construction concepts that should both take place in ECN process. Finally, a general description of the Problem Flow Networks (PFN) approach based on OTSM-TRIZ technologies is given to show how it could be used within ECN process.